Accommodation Facilities' Localisation and Seasonality in The South Bohemian Region - Petra MARTISKOVA; Tereza WALDHAUSEROVA; Petra VYSUSILOVA; Roman SVEC (Communications of International Proceedings, 2022)
Our contribution aims to map out and analyse the structure of the accommodation facilities offered in the investigated tourist area of South Bohemia. Our main task was to examine the primary characteristics of accommodation facilities and closely examine the facilities' products. The data was collected through an online survey, destination and accommodation websites' search and a field survey. The data collected specifies the accommodation facility type, classification, seasonality, method of operation and size of the accommodation facility, and price per bed for one night without breakfast. Among the product characteristics, particularly the claim about the ecological behaviour of the facility was examined. This study deepens the understanding of the distribution and nature of the accommodation offer in the tourism industry. Our research uncovered a number of accommodation facilities missing in official statistics of the area. The findings also contribute to the efforts of regional companies, destination organisations and the local government in better cataloguing and managing the accommodation offered in the studied area.
Keywords: accommodation; tourism; guest; localisation.